Modified fine blanking of cam-shaped profile using a double-action hydraulic press. Issue 6 (26th April 2019) - Aravind, U.; Uday, C.; Venugopal, P.
ABSTRACT: Blanking is a single stroke sheet metal cutting process that produces blanks with closed contour profiles. Fine blanking is a more precise version of this process that produces near-net products that require minimal post-forming finish machining operations. The process of fine blanking generally requires a triple action press. In the present work, fine blanking of a non-rotational symmetric profile using a double-action press while using rubber to apply counterforce has been investigated for four commonly used sheet metals viz. commercially pure aluminum, α-brass, extra deep drawing (EDD) steel and 304 grade stainless steel (SS304). Edge quality and product flatness while using rubber to apply counterforce were found to be meeting fine blanking quality standards. Percentage smooth shear and burr were found to be independent of material properties. Die roll, dishing and tearing behavior were found to be dependent on material properties. The effect of counterforce on the product quality was investigated by conducting experiments without counterforce. An empirical relation that relates the dishing tendency of a material (in the absence of counterforce) to its mechanical properties was developed.